Den Norske Sydpol-ekspedisjonen 1990-91 (Polarboken, 1992)
Keywords: Antarktis; ekspedisjoner

Søker fortiden og framtiden på Sydpolen - Bakka, Toril (Statoil magasin, 1992)
Keywords: Antarktis; biografi; ekspedisjoner

Phytoplankton distribution in relation to sea ice, hydrography and nutrients in the northwestern Weddell Sea in early spring 1988 during EPOS - Bianchi, Franco; Boldrin, Alfredo; Cioce, F; Dieckmann, Gerhard Stephan; Kuosa, Harri; Larsson, A M; Nöthig, Eva-Maria; Sehlstedt, P I; Socal, Giorgio; Syvertsen, Erik E (Polar Biology, 1992)
Phytoplankton biomass and distribution of major phytoplankton groups were investigated in relation to sea ice conditions, hydrography and nutrients along three north-south transects in the north western Weddell Sea in early spring 1988 during the EPOS Study (European Polarstern Study), Leg 1. Three different zones along the transects could be distinguished: 1) the Open Water Zone (OWZ) from 58-degrees to 60-degrees-S with high chlorophyll a concentrations up to 3.5-mu-g l-1; 2) the Marginal Ice Zone (MIZ) from 60-degrees to about 62.5-degrees with chlorophyll a concentrations between 0.1 and 0.3-mu-g l-1, and 3) the closed pack-ice zone (CPI) from 62.5-degrees to 63.2-degrees-S with chlorophyll a concentrations below 0.1-mu-g l-1. Nutrient concentrations increased towards the south showing winter values under the closed pack-ice. Centric diatoms such as Thalassiosira gravida and Chaetoceros neglectum forming large colonies dominated the phytoplankton assemblage in terms of biomass in open water together with large, long chain forming, pennate diatoms, whereas small pennate diatoms such as Nitzschia spp., and nanoflagellates prevailed in ice covered areas. Fairly low concentrations of phytoplankton cells were encountered at the southernmost stations and many empty diatom frustules were found in the samples. The enhanced phytoplankton biomass in the Weddell-Scotia-Confluence area is achieved through sea ice melting in the frontal zone of two different water masses, the Weddell and the Scotia Sea surface waters.
Keywords: Sørishavet; Weddellhavet; biomasse; diatomeer; fytoplankton; havis; hydrografi; marin biologi; oseanografi

Ecology of sea ice biota. 1. Habitat, terminology, and methodology - Horner, Rita; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjorn; Hoshiai, Takao; Legendre, Louis; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
Polar regions are covered by extensive sea ice that is inhabited by a variety of plants and animals. The environments where the organisms live vary depending on the structure and age of the ice. Many terms have been used to describe the habitats and the organisms. We here characterize the habitats and communities and suggest some standard terms for them. We also suggest routine sampling methods and reporting units for measurements of biological and chemical variables.
Keywords: Sørishavet; biodiversitet; havis; marin biologi; polarområdene; økologi

Do glaciers tell a true atmospheric CO2 story? - Jaworowski, Zbigniew; Segalstad, Tom Victor; Ono, Nobuo (Science of The Total Environment, 1992)
Until 1985 most studies of CO2 in gas inclusions in pre-industrial ice indicated that CO2 concentrations (up to 2450 ppm) were higher than the current atmospheric level. After 1985, lower pre-industrial CO2 values were reported, and used as evidence for a recent man-made CO2 increase. The errors in these revised values, however, are of a similar magnitude to the apparent increase in atmospheric CO2 level. The assumptions used in estimating lower CO2 values in past atmospheres have been: no liquid phase in polar ice; younger age of air than of ice due to free gas exchange between deep firn and the atmosphere; and no change in composition of air inclusions. These assumptions are shown to be invalid. Liquid saline water exists in ice at low temperatures, even below −70°C; airtight ice layers are ubiquitous in Antarctic firn; and more than 20 physico-chemical processes operating in situ and in ice cores contribute to the alteration of the chemical composition of air inclusions. The permeable ice sheet with its capillary liquid network acts as a sieve which redistributes elements, isotopes, and micro-particles. Thirty-six to 100% of air recovered from old ice is contaminated by recent atmospheric air during field and laboratory operations. The value of ∼290 ppm, widely accepted from glacier studies for the pre-industrial atmospheric CO2 level, apparently results from: invalid assumptions; processes in ice sheets; artifacts in ice cores; and arbitrary rejection of high readings. To date, glaciological studies are not able to provide a reliable reconstruction of either the CO2 level in pre-industrial and ancient atmospheres or paleoclimates. Instead these studies have led to a widely accepted false dogma of man-made climatic warming. This dogma may have enormous negative impact on our common future.
Keywords: Antarktis; drivhuseffekt; glasiologi; global oppvarming; isbreer; karbondioksid; paleoklimatologi; stabile isotoper

Activities within the Aurora Programme field season 1991/92 - Kristensen, Monica (Filchner-Ronne Ice Shelf Programme. Report, 1992)
Keywords: Antarktis; ekspedisjoner; glasiologi; meteorologi

Nitrogen uptake in the Weddell Sea during late winter and spring - Kristiansen, Svein; Syvertsen, Erik E; Farbrot, Tove (Polar Biology, 1992)
Keywords: Sørishavet; Weddellhavet; alger; biologi

Glaciomarine turbidite and current controlled deposits in Prydz Bay, Antarctica - Kuvaas, Berit; Leitchenkov, German (Marine Geology, 1992)
A thick sequence (up to 2200 m) of presumed post late Eocene/early Oligocene glaciomarine sediments is inferred to be present on the Prydz Bay continental rise. In the absence of information from drillholes, we correlate to ODP Leg 119 drillsites on the shelf and compare with the seismic reflection pattern of glaciomarine sequences in the Weddell Sea. The inferred glaciomarine sediments in Prydz Bay appear to be deposited in a complex manner, suggesting interaction by both turbidity cur rents and strong bottom currents. Reflection seismic profiles from the lower continental slope and rise shows an abundance of current influenced deposits, such as sediment waves and large sediment ridges with similarities to contourite drifts. In addition, large channel-levee complexes are abundant, suggesting deposition by turbidity currents and other massflow processes. Large channels and sediment ridges trend oblique to the continental margin. The geometry and character of the seismic reflection pattern suggest that the ridges have been deposited under the combined influence of overflow from downslope channelized turbidity currents and strong bottom water flow. The observed sediment waves and the difference along eastern and western channel margins suggest that bottom currents are flowing towards the west. We suggest that the initiation of turbidite sedimentation occurred in the late Eocene-early Oligocene, when the Amery Ice Shelf reached the shelf edge for the first time. Onset of current controlled deposition may possibly be related to the opening of the Drake Passage at the Oligocene/Miocene boundary.
Keywords: Sørishavet; Weddellhavet; havbunnen; kontinentalmargin; marin geologi

Ecology of sea ice biota. 2. Global significance - Legendre, Louis; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjørn; Horner, Rita; Hoshiai, Takao; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
The sea ice does not only determine the ecology of ice biota, but it also influences the pelagic systems under the ice cover and at ice edges. In this paper, new estimates of Arctic and Antarctic production of biogenic carbon are derived, and differences as well as similarities between the two oceans are examined. In ice-covered seas, high algal concentrations (blooms) occur in association with several types of conditions. Blooms often lead to high sedimentation of intact cells and faecal pellets. In addition to ice-related blooms, there is progressive accumulation of organic matter in Arctic multi-year ice, whose fate may potentially be similar to that of blooms. A fraction of the carbon fixed by microalgae that grow in sea ice or in relation to it is exported out of the production zone. This includes particulate material sinking out of the euphotic zone, and also material passed on to the food web. Pathways through which ice algal production does reach various components of the pelagic and benthic food webs, and through them such top predators as marine mammals and birds, are discussed. Concerning global climate change and biogeochemical fluxes of carbon, not all export pathways from the euphotic zone result in the sequestration of carbon for periods of hundreds of years or more. This is because various processes, that take place in both the ice and the water column, contribute to mineralize organic carbon into CO2 before it becomes sequestered. Processes that favour the production and accumulation of biogenic carbon as well as its export to deep waters and sequestration are discussed, together with those that influence mineralization in the upper ice-covered ocean.
Keywords: Sørishavet; biodiversitet; biogeokjemi; havis; karbondioksid; klimaendringer; marin biologi; polarområdene; økologi

Negotiating the mineral regime in the Antarctic: a review - Mørkved, Berit (International Challenges, 1992)
Keywords: Antarktis; jus; mineraler; politikk

Gigantisk isfjell i Sør-Atlanteren - Orheim, Olav (Polarboken, 1992)
Keywords: Sørishavet; glasiologi; isfjell

Studies through Jutulgryta, Fimbulisen in the 1991/92 season - Østerhus, Svein; Orheim, Olav (Filchner-Ronne Ice Shelf Programme. Report, 1992)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis; oseanografi

Pertusaria signyae (Lichenes), a new species from the Antarctic - Øvstedal, Dag Olav; Smith, Ronald I Lewis (Nova Hedwigia, 1992)
A saxicolous Pertusaria species is described as new to science: P. signyae Ovst. from South Orkney Islands. It has an isidiate thallus, subglobose fertile verrucae with poriform apothecia, and contains 2'-0-methylperlatolic acid.
Keywords: Antarktis; Sør-Orknøyene; botanikk; lav; planter

Determination of sulphur- and chlorine-containing compounds using capillary gas chromatography and atomic emission detection - Pedersen-Bjergaard, Stig; Asp, Tone Normann; Greibrokk, Tyge (Analytica Chimica Acta, 1992)
The potential of universal calibration using capillary gas chromatography combined with atomic emission detection was evaluated for several chlorine- and sulphur-containing compounds of environmental interest. The elemental responses obtained for C, H, Cl and S were found to be affected by the molecular structure. Rapid determination of several analytes was accomplished using a single calibration graph based on one randomly selected reference compound, but 10–30% errors relative to the actual concentrations were observed in several instances. The results were significantly improved by using reference compounds with structures similar to those of the analytes of interest. the practical utility of universal calibration is illustrated by the determination of pesticides in stomach oil deposits from birds living in Antarctica.
Keywords: Antarktis; biokjemi; fugler; kjemi; kromatografi; petreller

Contributions to the Caloplaca flora of the western Antarctic region - Søchting, Ulrik; Øvstedal, Dag Olav (Nordic Journal of Botany, 1992)
Fourteen species of the lichen genus Caloplaca are recorded from the western Antarctic region and described morphologically and anatomically, viz.: C. ammiospila, C. approximata, C. athallina, C. cirrochrooides, C. citrina, C. isidioclada, C. lucens, C. millegrana, C. regalis, C. sublobulata, C. tenuis, C. aff. anchon-phoeniceon. Type specimens of critical species have been studied. A key is provided to the species. Caloplaca ammiospila and C. approximata are reported as new to the Antarctic region.
Keywords: Antarktis; botanikk; lav; planter

Bouvetøya: et norsk naturreservat - Sømme, Lauritz (Fauna, 1992)
Keywords: Bouvetøya; fauna; forvaltning; natur

Protecting the frozen south - Stokke, Olav Schram (Green globe yearbook, 1992)
Keywords: Antarktis; jus; miljøvern; politikk

Eine neue Gyalecta-Art aus der Antarctis: G. pezizoides sp. n. (lichensierte Fungi, Gyalectaceae) - Vezda, A.; Øvstedal, Dag Olav; Smith, Ronald I Lewis (Nova Hedwigia, 1992)
A new species of the genus Gyalecta, G. pezizoides sp. n. (lichenized Fungi, Gyalectaceae), is described and illustrated. This new species is taxonomically near to the holarctic Gyalecta peziza (Mont.) Anzi.
Keywords: Antarktis; botanikk; lav; planter

Vel blåst! Kommandør Chr. Christensens Hvalfangstmuseum gjennom 75 år 1917-1992 - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1992)
Keywords: Antarktis; Christen Christensen; Nordmenn; Vestfold; historie; hvalfangere; hvalfangstindustri; pelagisk; polarekspedisjoner